E4orf1: A protein for enhancing glucose uptake despite impaired proximal insulin signaling - Shastri, Anuradha A. (PLoS One, 2018)
BACKGROUND: Type 2 diabetes is often linked with impaired proximal insulin signaling. Hence, a therapeutic agent that enhances cellular glucose uptake without requiring proximal insulin signaling would be desirable for improving glycemic control. The E4orf1 peptide (E4) derived from human adenovirus 36 (Ad36) promotes cellular glucose uptake in vitro and in vivo, independent of insulin. E4 bypasses a part of insulin signaling to upregulate cellular glucose uptake. We tested the hypothesis that E4 requires the distal but not proximal insulin signaling to enhance cellular glucose disposal. METHODS: 3T3-L1 preadipocytes inducibly expressing E4 or a null vector (NV) were treated with inhibitor of insulin receptor (S961), inhibitor of insulin like growth factor-1receptor (IGF-1R) (Picropodophyllin, PPP), PPP+S961, or phosphatidyl inositol-3 kinase (PI3K) inhibitor (Wortmannin, WM). We used PPP and S961 to block the proximal insulin signaling, or WM to block the distal insulin signaling. Cells were exposed to 0 or 100nM insulin. RESULTS: As expected, when the proximal or distal insulin signaling was blocked in NV cells, insulin could not enhance pAKT protein abundance, Glut4 translocation, or glucose uptake. Whereas, E4 cells significantly increased pAKT abundance, Glut4 translocation and glucose uptake independent of the presence of insulin or proximal insulin signaling. Enhanced glucose disposal in E4 cells was completely abrogated when the distal insulin signaling was blocked. CONCLUSIONS: E4 bypasses the proximal insulin signaling but uses the distal insulin signaling to activate pAkt and in turn Glut4 translocation to improve cellular glucose uptake. E4 offers a promising template to improve glycemic control when the proximal insulin signaling is impaired.